Constraints Affecting Fertility of Sex Sorted Semen: An Overview - MS, Roshan Krishna; Suthar, Babulal Natvarlal; Nakhashi, Hareshbhai Chhotalal; Chaudhary, Karan Faljibhai (The Indian Journal of Animal Reproduction, 2022)
In most mammals, the male to female sex ratio of offspring is about 50% because half of the sperm contains either the Y chromosome or the X chromosome. Desired sex either male or female which is produced from semen having X or Y bearing sperm is known as sexed semen. Flow cytometry is the only proven method for semen sexing to be commercially viable with more than 90% accuracy to produce calves of desirable sex. The sexed semen technology has several advantages, the production of more female calves and more milk, and lowered risk of dystocia. Increased efficiency of progeny testing, embryo transfer and in-vitro fertilization program has proposed a demand of feasible technology for sex sorting of spermatozoa. In India, this revolutionary technology is in its budding stage. This paper aimed to review the constraints affecting the fertility of sex sorted semen.
Keywords: Chromosome; Flow cytometry; sexed semen